In vitro screening for drought tolerance of some chickpea varieties in Bangladesh (Progressive Agriculture, 2016)
The aim of the present study was to study physiological response of seven chickpea varieties viz. Binachola-2, Binachola-3, Binachola-4, Binachola-5, Binachola-6, Binachola-7 and Binachola-8 at different levels of drought stress induced by polyethylene glycol (PEG).  Five different concentrations (0, 20, 35, 50, 60 g/L) of PEG 6000 was added in MS medium to create five different levels of drought stress for  in vitro screening of drought tolerant chick pea varieties. Data were recorded on germination percentage, fresh weight, shoot length, root length, dry weight, turgid weight, relative water content (RWC) and proline content. The seven chickpea varieties differed significantly for different parameters in response to the drought stress. Binachola-2 and Binachola-7 showed the best performance for all the parameters studied. At the highest dose of PEG (60 g/l), in the most water deficient condition, fresh weight was recorded 0.59 g and 0.84 g, Shoot lengths of 2.10 cm and 3.75 cm, root lengths of 1.15 cm and 1.00 cm, turgid weight of 0.960 g and 0.970 g, dry weight of 0.13 g and 0.21 g, relative water contents (RWC) of 85.71% and 83.33% were recorded in Binachola-2 and Binachola-7, respectively. Increased proline content was recorded with the increasing level of PEG concentration. Proline content 0.533g/100g FW and 0.598g/100g FW were observed in Binachola-2 and Binachola-7, respectively under the influence of PEG at 60 g/l. Data recorded for Binachola-3, Binachola-4, Binachola-5, Binachola-6 and Binachola-8 for the studied parameters revealed that they showed susceptible response against higher drought stress level generated by PEG. The data of this experiment revealed that, the accumulation of proline was significantly greater under drought stress. Thus, it is evident that Binachola-2 and Binachola-7 performed better against drought stress condition. These results of physiological and biochemical parameters may be utilized as a selection indicator for breeding program and used as a baseline for improvement of chickpea varieties in Bangladesh.Progressive Agriculture 27 (2): 110-118, 2016